Households' awareness, attitudes and practices regarding waste cooking oil recycling in Petaling, Malaysia - Kabir, Ibrahim; Yacob, Mohd Rusli; Radam, Alias (International Organization of Scientific Research, 2014)
Cooking oil as an additive and medium of heat transfer plays a significant role in food preparation. Its attributes of providing food with good taste, colour and aroma gave it general acceptance among consumers. In recent years, huge amount of waste cooking oil (WCO) is generated and discharged in to the environment in various countries of the world. This study examined empirically the households’ awareness, attitudes and practices towards WCO recycling in Petaling District of Selangor State, Malaysia. Information on households’ awareness, attitudes and practices regarding WCO reuse, recycling and disposal will give a hint on how to improve WCO management in order to reduce its associated environmental problems. The study was conducted based on 352 households, who were randomly interviewed face-to-face using structured questionnaires from February to June, 2013. The results indicated that the average WCO generated per household is 2.34 kg/month, and even though the households’ awareness on the significance of WCO recycling were generally positive, only small portion of them are engaged into it. However the result of the logit regression revealed that awareness and attitude were the significant factors that influence households engagement into WCO recycling, there is need for intensifying efforts in creating more awareness on proper management of WCO. The researchers finally suggested ways on how to encourage WCO management among households in Petaling.